The Effect of the Implementation of Risk Management and Corporate Governance with Stock Performance as a Variable Intervening on the Financial Performance of Banking (Analytic Study on Commercial Banking Listed on the Indonesia Stock Exchange) - Khalisah Visiana; Yednista Agnes Tidore (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine whether Risk Management and GCG with stock performance as an intervening variable on the financial performance of banking companies listed on the IDX to find out whether Risk Management and GCG affect the financial performance of banking companies listed on the IDX through stock performance as an intervening variable, to find out whether Risk Management and GCG affect stock performance in banking companies listed on the IDX and to determine whether stock performance has an effect on financial performance at the IDX. Banking companies are listed on the Stock Exchange. The population used in this study are banking companies listed on the Stock Exchange, as many as 43 companies using the purposive sampling method. There are 19 banking companies, with the year 2016-2020 observations. However, to measure discretionary accruals plus the 2015 observation year, 95 observations were obtained as sampling in this study. Hypothesis testing was carried out by linear regression analysis. Has a significant effect on financial performance. The application of risk management by using stock performance as an intervening variable cannot mediate on financial performance, GCG by using stock performance as an intervening variable cannot mediate on company performance, meaning that stock performance is not a good variable in mediating the relationship between Risk Management, GCG with Financial Performance (KK), and Risk Management has an effect on stock performance, GCG has an effect on stock performance and stock performance affects financial performance.